Ferroelectric performance, surface and mechanical properties of poled PVDF sheet with metal coating: Assessing through PFM, FTIR, and nanoindentation and nanoscratch. (27th July 2017) - Liu, Yizhi; Sun, Yi; Zeng, Fanlin
ABSTRACT: In this work, the poled PVDF with metal coating was prepared. The microscopy characterization and crystalline phase were studied. The piezoresponse force microscope (PFM) test, nanoindentation and nanoscratch tests were carried out. The focus of this work is on the morphology, local piezoelectric deformation, and the key properties of PVDF sheet with coating, such as the hardness, roughness, critical load and so on. The aim is to determine surface characteristic, ferroelectric domain and mechanical properties of PVDF sheet and can avoid the unfavorable effect that the sample served as an actuator broke during the bending deformation.